EDUKASI PENTINGNYA 1000 HARI PERTAMA KEHIDUPAN ANAK SEBAGAI UPAYA PENCEGAHAN STUNTING - Simamora, Marthalena; Sinaga, Janno; Silitonga, Rosita (Universitas Sari Mutiara Indonesia, 2022)
Stunting or short is a condition of failure to thrive in children under five years of age (toddlers) due to chronic malnutrition and repeated infections, especially in the first 1,000 days of life (HPK), from fetus to child aged 23 months. Children are classified as stunted if their length or height is below minus two standard deviations of length or height of children their age. Stunting is a major threat to the quality of Indonesia's Human Resources (HR), as well as a threat to the nation's competitiveness. This is because children who fail to grow are not only disturbed by their physical growth, but also have impaired brain development, which of course will greatly affect their ability and achievement in school, as well as productivity and creativity in productive ages. The purpose is to prevent an increase in the incidence of stunting in toddlers. This activity is carried out in the form of health promotion through education about the first 1000 days of a child's life using the lecture method. The target of this activity is pregnant women. This activity was attended by 33 pregnant women and mother of toddler. The results of the evaluation showed that the knowledge of the activity participants increased after the education was carried out. Increased knowledge is in line with increasing public awareness of the importance of the 1000 HPK period so that it is expected that the prevalence of stunting increases can be prevented.